2011
DOI: 10.1002/mabi.201100097
|View full text |Cite
|
Sign up to set email alerts
|

Size‐Controlled Nanoassemblies Based on Cyclodextrin‐Modified Dextrans

Abstract: Nanoassemblies formed by host/guest interactions between two polymers in aqueous media are studied. Two types of polymers with the same dextran backbone are modified with adamantyl or βCD groups. The sizes of the spontaneously formed nanoassemblies depend on the βCD:Ada ratio and on the total concentration and composition of the mixtures. The results can be rationalized by assuming a core/shell structure of the nanoassemblies, the core resulting from associative phase separation of the two polymers and being s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0
1

Year Published

2012
2012
2015
2015

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(35 citation statements)
references
References 33 publications
1
33
0
1
Order By: Relevance
“…It might be explained by the presence of relatively long and hydrophilic spacer in D40-GP-Ada-PEG, the latter making adamantyl groups more loosely attached and available for complexation. As in the reference (Wintgens et al, 2011), a slight decrease of K a is observed while increasing the substitution degree by Ada-groups from 5 to 10 mol%, which could be attributed to a gradual loss of their accessibility due to steric effects.…”
Section: Itc Studiessupporting
confidence: 69%
See 3 more Smart Citations
“…It might be explained by the presence of relatively long and hydrophilic spacer in D40-GP-Ada-PEG, the latter making adamantyl groups more loosely attached and available for complexation. As in the reference (Wintgens et al, 2011), a slight decrease of K a is observed while increasing the substitution degree by Ada-groups from 5 to 10 mol%, which could be attributed to a gradual loss of their accessibility due to steric effects.…”
Section: Itc Studiessupporting
confidence: 69%
“…The different thermodynamic parameters derived from these experiments are given in Table 2. The association constants are as high as 4.0-6.0 × 10 4 L/mol, which is superior to previously described dextrans modified with Adagroups via simple esterification by 1-adamantanecarbonyl chloride (Wintgens et al, 2011). It might be explained by the presence of relatively long and hydrophilic spacer in D40-GP-Ada-PEG, the latter making adamantyl groups more loosely attached and available for complexation.…”
Section: Itc Studiesmentioning
confidence: 55%
See 2 more Smart Citations
“…La fase gel presenta una alta concentración de ambos polímeros, con valores de G´ y G´´ 400-500 Pa y 1200-1400 Pa, respectivamente [81,82]. Si las concentraciones de polímeros son más bajas (0.1-1% p/p) se forman partículas nanométricas de tamaño variable según el grado de sustitución del polímero con grupos que forman complejos con las CDs [83,84]. Si los polímeros cuentan con grupos ionizables, se pueden conseguir geles de viscosidad variable en función del pH del medio.…”
Section: Cds Libres En Entramados Poliméricosunclassified